PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN GURU MENGAJAR DAN PEMANFAATAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR IPS TERPADU - Devi Yulianti; Darwin Bangun; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
The purpose of this study was to determine the effect of students 'perceptions of teachers' teaching skills and utilization of instructional media on student learning outcomes IPS Terpadu eighth grade students of SMP Negeri 2 Panaragan Jaya, Tulang Bawang Tengah Academic Year 2012/2013. The population in this study were eighth grade students of SMP Negeri 2 Tulang Bawang Tengah as much as 3 classes totaling 107 students. Using the formula with probability sampling T.Yamanne sample obtained 84 students. The method used in this research is verification with ex post facto approach. The problem in this study is whether there was an effect on students 'perceptions of teachers' teaching skills and utilization of instructional media on learning outcomes IPS Terpadu eighth grade students of SMP Negeri 2 Tulang Bawang Tengah Academic Year 2012/2013. Based on the analysis of the results obtained show that, (1) there is an influence on students 'perceptions of teachers' teaching skills learning outcomes IPS Terpadu eighth grade students of SMP Negeri 2 Tulang Bawang Tengah Academic Year 2012/2013, (2) effect on the results of the use of instructional media IPS Terpadu learning eighth grade students of SMP Negeri 2 Tulang Bawang Tengah Academic Year 2012/2013, (3) influence students 'perception of teachers' teaching skills and utilization of instructional media on learning outcomes IPS Terpadu eighth grade students of SMP Negeri 2 Tulang Bawang Tengah Academic Year 2012 / 2013.